DISHARMONY IN THE REGULATION OF MORTGAGE EXECUTION IN THE PROCESS OF DEBT PAYMENT OBLIGATION SUSPENSION AND BANKRUPTCY - Fidji Muhammad Sobar; Yeni Nuraeni; Eka Ardianto Iskandar (Awang Long Law Review, 2026)
Suspension of Debt Payment Obligations (PKPU) under Law Number 37 of 2004 concerning Bankruptcy and PKPU is designed as a legal mechanism to facilitate fair and efficient debt restructuring while preventing business collapse. PKPU grants a temporary moratorium of up to 270 days for debtors to propose a composition plan to creditors. However, a normative conflict arises between the rights of secured creditors under Law Number 4 of 1996 concerning Mortgage Rights and the provisions of the Bankruptcy/PKPU Law. Article 6 of the Mortgage Law authorizes first-ranking mortgage holders to execute collateral through auction upon debtor default, whereas Article 245 of the Bankruptcy/PKPU Law restricts debt payments, including proceeds from collateral execution, prior to the approval of a composition plan (homologation) or a declaration of bankruptcy, except on a proportional basis to all creditors. This study employs normative juridical research using statutory, conceptual, and case approaches to analyze the disharmony between these regulations and its implications for legal certainty. The findings indicate that the suspension of execution rights during PKPU creates uncertainty and weakens the position of secured creditors, potentially conflicting with the principle of material security rights. Therefore, regulatory harmonization is necessary to balance the protection of secured creditors’ rights with the restructuring objectives of PKPU, thereby ensuring legal certainty and fairness within Indonesia’s insolvency framework.